Rapid characterization of graded alloys fabricated by 3D printing - Bella Lee Hoondal (Nanyang Technological University, 2023)
3D printing has revolutionized the fabrication of metals and alloys in both academic and industrial areas, due to its advantages of one-step manufacturing into complex shapes without the need for post thermomechanical processing. However, fabrication defects, e.g., porosity, cracking, and delamination, severely limit the materials library for 3D printing. Therefore, it is of great significance to address the fabrication issues and/or conduct high-throughput composition screening to develop alloys that are amenable to the 3D printing process. One class of materials of particular interest is Cu-based alloys, renowned for their excellent combination of electrical conductivity and mechanical properties. However, Cu is highly reflective to the laser commonly used in 3D printing, which makes it challenging to be fully melted and then fabricated without evident defects. One of the promising approaches is to incorporate sufficient amount of alloying element to enhance the laser absorptivity. Nevertheless, the electrical conductivity of Cu alloys is sensitive to the content of alloying element and thus leads to a dilemma between printability and property. To address this issue, it is important to screen out the critical content of alloy element that allows for reliable printing without compromising the electrical properties. In this endeavour, 3D printing allows for the printing of multiple Cu-based alloy samples. These samples are subjected to meticulous characterization and porosity studies, marking a critical phase in the journey to identify optimal parameters and compositions. Researchers aim to maintain the good mechanical and electrical properties of Cu while minimizing porosity, a fundamental goal in 3D printing. This iterative process of printing, characterizing, and refining materials paves the way for the development of Cu-based alloys with superior properties. In conclusion, 3D printing's capabilities empower scientists to tackle the challenges posed by materials like Cu. Achieving good density and low porosity in these alloys is the ultimate objective, and characterization plays an indispensable role in this pursuit. This research not only contributes to our understanding of 3D printing materials but also opens doors to innovative applications of Cu and its alloys in various industries, from electronics to manufacturing.